Disseminated malignant phaeochromocytoma: localisation with iodine-131-labelled meta-iodobenzylguanidine. Issue 6349 (23rd October 1982) - Sutton, H; Wyeth, P; Allen, A P; Thurtle, O A; Hames, T K; Cawley, M I; Ackery, D
Abstract : Meta-iodobenzylguanidine, a guanethidine analogue, is a newly synthesised substance capable of imaging the adrenal medulla. In a woman in whom phaeochromocytoma has been diagnosed iodine-131-labelled metaiodobenzylguanidine was given intravenously; gamma-camera images showed bilateral adrenal tumours and uptake corresponding to bone and liver metastases. 131I-meta-iodobenzylguanidine is effective in localising phaeochromocytomas, and the technique is safe, specific, and non-invasive.